2016
DOI: 10.4314/gjss.v14i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Interest rate and commercial banks’ lending operations in Nigeria: A structural break analysis using chow test

Abstract: This study used the classical least squares method to empirically examine interest rate deregulation effect on the lending operations of Nigerian commercial banks for the period 1970 to 2013. The period was divided into two policy regime periods; the regulated interest rate era spanning 1970-1986 and the deregulated period 1987-2013. The Chow test was applied to examine if there was any significant difference in the relationship between interest rate and commercial banks' lending for the two periods. The empir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Similar results were recorded during the study conducted by Bhattarai (2016) where he found that liquidity ratio correlated negatively with the capital reserve and bank size, somehow collaborating indicators to exchange rates and interest rate spread. In contrast, Eke (2015) reported from his study in Nigeria that there seems to be higher IRS only when there are trends of increasing exchange rate and interest rate spread but with decreasing inflation. This phenomenon could better be conceptualized with the affinity of the borrowers towards low risk of inflation as the major investment these days have, in one way or the other, related to international trade and market.…”
Section: Correlation Analysismentioning
confidence: 76%
“…Similar results were recorded during the study conducted by Bhattarai (2016) where he found that liquidity ratio correlated negatively with the capital reserve and bank size, somehow collaborating indicators to exchange rates and interest rate spread. In contrast, Eke (2015) reported from his study in Nigeria that there seems to be higher IRS only when there are trends of increasing exchange rate and interest rate spread but with decreasing inflation. This phenomenon could better be conceptualized with the affinity of the borrowers towards low risk of inflation as the major investment these days have, in one way or the other, related to international trade and market.…”
Section: Correlation Analysismentioning
confidence: 76%
“…It continued to increase, reaching 4.25 percent between 2000 and 2006, before the banking consolidation reform, and reached 7.39 percent after the reform until the review period of 2020. The financial liberalization theory's theoretical tenet that "high level of interest rates enhances the level of financial deepening" is supported by a considerable interest rate, according to Eke and Inyang (2015). Interest rates are not a reliable indicator of financial repression, according to De Gregorio and Guidotti (1995).…”
Section: Presentation Of Results and Discussionmentioning
confidence: 99%
“…In addition, there are three methods of estimating the regression model using panel data, namely: random effects model based on data characteristics. To select the Panel data regression model, we used the Chow test (Eke, Eke, & Inyang, 2016;Nielsen & Whitby, 2015), Hausman test (Ahn & Moon, 2014;Aït-Sahalia & Xiu, 2019), and Lagrange multiplier test (Chen et al, 2021;Li & Yao, 2021). The regression model (Bernasconi et al, 2021;Sparapani et al, 2021): Hypothesis testing is using the coefficient of determination (adjusted R2), F test, and T test with each probability less than 0.05 (Ongan et al, 2020).…”
Section: -Dependent Variable (Variable Y): Pbvmentioning
confidence: 99%